Frequency of Adverse Effects of Fixed Dose Combinations, in Tuberculosis and there Effects on Treatment Outcome (SAARC Journal of Tuberculosis, Lung Diseases and HIV/AIDS, 2016)
Introduction: This study was designed to assess the frequency, types and impact of adverse drug reactions (ADR) to category 1 anti-tubercular therapy using fixed drug combinations (FDC). Patients with tuberculosis started on anti TB treatment from 01st of July 2011 to 30th of June 2012 were recruitedMethodology: Patients were followed up for development of ADR. Frequency of ADR, number of patients who required prolongation of therapy, who had alternate regimes, and there treatment outcome were recorded.Results: Out of 280 patients with tuberculosis 67 (24%), 37 (55.2%) males, 30 (44.8%) females ADR. Thirty three out of 74 (44%) of total population above the age of 60 had ADR, while only 34 out of 206 (16.5%) of patients below the age of 60 had ADR (Chi= 23, p